Ethnic differences in risk markers for heart disease in Bradford and implications for preventive strategies. Issue 2 (April 1993) - Knight, T; Smith, Z; Lockton, J A; Sahota, P; Bedford, A; Toop, M; Kernohan, E; Baker, M R
Abstract : OBJECTIVES–To assess and compare the prevalence of established risk markers for ischaemic heart disease in a sample of Asian and non-Asian men and to relate these observations to preventive strategies. SETTING–Two factories in the textile industry in Bradford, West Yorkshire, UK. Subjects–288 male manual workers aged 20 to 65 years. DESIGN–Cross sectional study within one occupational/social class stratum. MEASUREMENTS AND MAIN RESULTS–Age, body mass index, plasma lipids, fibrinogen and serum insulin values, blood pressure, smoking habits, alcohol consumption, and exercise routines were recorded. Plasma total cholesterol concentrations were significantly lower in Asian than non-Asian men (5.3 mmol/l v 5.8 mmol/l respectively, p < 0.0001), as were low density lipoprotein cholesterol concentrations (3.4 mmol/l v 3.7 mmol/l, p = 0.0150), and high density lipoprotein (HDL) cholesterol (1.1 mmol/l v 1.3 mmol/l, p < 0.0001). Hypercholesterolaemia (concentration > 6.5mM) was present in nearly one quarter of non-Asians but less than one eighth of Asian men. Triglyceride values were not significantly higher in Asians. Smoking rates were high in non-Asians (43.8%) and only slightly lower in Asians (39.1%). Asian smokers smoked fewer cigarettes per day on average (9.3 v 16.1, p = 0.0001). Almost a quarter of non-Asian men (23.1%) and 26.6% of Asian men had raised blood pressure. Systolic pressures were higher in non-Asian men (138.3 mmHg v 133.0 mmHg, p = 0.0070), but diastolic pressures showed no ethnic differences. Diabetes was more prevalent in Asian men (10.9% v 4.4% p < 0.05), who also showed higher serum insulin concentrations after glucose loading (22.3 mU/l v 10.2 mU/l, p < 0.0001). Plasma fibrinogen values were higher in non-Asian men (2.9 g/l v 2.6 g/l, p < 0.0001) and these were associated with smoking. Nearly all non-Asians (92.5%) consumed alcohol at some time whereas 62.5% of Asians habitually abstained from alcohol consumption. Among the drinkers, non-Asian men consumed on average, 23.9 units per week and Asian men 18.4 units per week (p = 0.083). The mean body mass index for Asian men was 24.5 kg/m2 which was not significantly different to the mean in non-Asian men (25.2 kg/m2). The frequency of exercise in leisure time was low in both groups with 44.4% of non-Asian and 21.1% of Asian men taking moderate exercise weekly, and even fewer, regular strenuous exercise (16.3% and 8.6% respectively). CONCLUSIONS–The plasma cholesterol and fibrinogen concentrations, prevalence of hypertension, smoking habits, alcohol intakes, and infrequency of exercise in leisure time in these non-Asian men in Bradford were consistent with an increased risk of heart disease. The pattern of risk markers was clearly different in Asian men. Only their lower HDL cholesterol concentrations, marginally higher triglyceride values, higher prevalence of diabetes, and very low frequency of exercise in leisure time would be consistent with a higher risk of heart disease compared with non-Asians. The implications of these observations for heart disease preventive strategies are discussed.